Association Between Serum Cystatin C and Thyroid Diseases: A Systematic Review and Meta-Analysis - Xin, Caihong; Xie, Jing; Fan, Huaying; Sun, Xin; Shi, Bimin (Frontiers in Endocrinology, 2021)
Abstract Background: Cystatin C (CysC) is often used to diagnose and monitor renal diseases. Although some studies have investigated the association between serum CysC levels and thyroid diseases, their reported results were inconsistent. Therefore, the relationship between CysC levels and thyroid diseases remains controversial. Aim: This meta-analysis aimed to statistically evaluate serum CysC levels in patients with thyroid diseases. Methods: A literature search was conducted using the PubMed, Web of Science, Embase, EBSCO, and Wiley Online Library databases. The following search terms were used for the title or abstract: “Cystatin C” or “CysC” in combination with the terms “thyroid disease,” “thyroid function,” “hypothyroidism,” or “hyperthyroidism.” The results of the systematic analysis were presented as standardized mean differences (SMDs) with corresponding 95% confidence intervals (CIs). Results: Eleven articles (1,265 cases and 894 controls) were included in the meta-analysis. The results of the meta-analysis showed that the serum CysC levels of patients with hyperthyroidism were significantly higher than those of the controls (SMD: 1.79, 95% CI [1.34, 2.25]), and the serum CysC levels of patients with hypothyroidism were significantly lower than those of the controls (SMD −0.59, 95% CI [−0.82, −0.36]). Moreover, the treatment of thyroid diseases significantly affected serum CysC levels. Conclusions: To the best of our knowledge, this meta-analysis is the first to evaluate serum CysC levels in patients with thyroid diseases. Our findings suggest that thyroid function affects serum CysC levels and that serum CysC may be an effective marker for monitoring thyroid diseases.